2017
DOI: 10.1186/s40635-016-0115-0
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Nlrp3 protects from inflammation-induced skeletal muscle atrophy

Abstract: BackgroundCritically ill patients develop atrophic muscle failure, which increases morbidity and mortality. Interleukin-1β (IL-1β) is activated early in sepsis. Whether IL-1β acts directly on muscle cells and whether its inhibition prevents atrophy is unknown. We aimed to investigate if IL-1β activation via the Nlrp3 inflammasome is involved in inflammation-induced atrophy.MethodsWe performed an experimental study and prospective animal trial. The effect of IL-1β on differentiated C2C12 muscle cells was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 53 publications
9
107
0
Order By: Relevance
“…Recently, we reported that SAA1 increases Il6 expression in murine and human myocytes in vitro . In addition, IL6 expression is increased in muscle of ICUAW patients and septic mice . We found that muscular TLR2 and TLR4 expression is increased during sepsis in patients and mice, that SAA1 increases Tlr2 and Tlr4 expression in myotubes, and that SAA1 via TLR2 and TLR4 increases Il6 expression in myocytes.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Recently, we reported that SAA1 increases Il6 expression in murine and human myocytes in vitro . In addition, IL6 expression is increased in muscle of ICUAW patients and septic mice . We found that muscular TLR2 and TLR4 expression is increased during sepsis in patients and mice, that SAA1 increases Tlr2 and Tlr4 expression in myotubes, and that SAA1 via TLR2 and TLR4 increases Il6 expression in myocytes.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, others and we showed that primarily fast‐twitch fibers undergo atrophy in ICUAW patients and septic mice . Therefore, we tested if BMS‐345541 protects fast/type‐II myofibers from atrophy in sepsis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations